A Descriptive Study On Students Ability In WritingNarative Text At The Second Year Of SMP N 1 TorohIn 2016/2017 Academic Year - NOVITASARI, YANI, Nur Hidayat, M.Pd (2016)
The aim of this study is to know the students' ability in writing narrative text, the content and organization of the narrative text, the students' vocabulary, grammar, and mechanism in writing narrative text at eight grade of SMP N 1 Toroh in 2016/2017 academic year. This research is a descriptive research. The object of this research is narrative text made by eight grade of SMP N 1 Toroh in2016/2017 academic year. The method of collecting data are writing text and analyzing document. Data of this research are the informant and writing test. The technique for analyzing data is (1) reading the students' work sheet in the form of narrative text. (2) Analyzing the aspects of narrative text: content, organization, vocabulary, grammar and mechanism. (3) Classifying and scoring the students test of writing narrative paragraph. (4) Drawing conclusion based on the research of the students' ability in writing narrative text. 16 students belong to good category (the score 75- 90) or 66, 67%. There are 5 students belong to fair category (the score 60-74) or 20, 83%. There are 3 students belong to poor category (the score 1-59) or 12, 5%, and there is no student belongs to excellent category. It means that the students' ability in writing narrative text at eight grade of SMP N 1 Toroh in 2016/2017 academic year is good. The most problem faces by the students in writing narrative are grammar. It can be seen from the average score of the aspects in narrative text.